The Effect of Education Finance On The Quality of Education In Indonesia - Agusniati, Andi (Devotion : Journal of Research and Community Service, 2023)
The quality of education is an important component that needs to be considered in order to achieve educational goals, there are several things that affect the quality of education in Indonesia, one of the factors is education financing which is also an important issue throughout the world. This study aims to determine the effect of education financing on the quality of education in Indonesia. This study uses a quantitative research method with a descriptive approach. Data collection techniques in this study used questionnaires and literature studies. The research data were then analyzed using the SPSS program. The results showed that education financing had an effect on the quality of education with a significance value of 0.000 and a proportion of 91%. Education funding affects the quality of education because it is very necessary for school programs, procurement of facilities and infrastructure, teacher salaries, employee salaries, the need to support the achievement of the school's vision and mission and create quality human resources